2011
DOI: 10.1001/archoto.2011.44
|View full text |Cite
|
Sign up to set email alerts
|

Association of Asthma With Clinically Aggressive Recurrent Respiratory Papillomatosis

Abstract: Patients with asthma, particularly those using daily inhaled corticosteroids, may have a more clinically aggressive RRP course. The cause of this association is unclear, and clinical recommendations should not yet be made based on these data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Given these results, it is important to understand intrinsic patient factors that affect patient susceptibility to RRP or severity of disease. Robb et al have reported evidence that the diagnosis of asthma, or its treatment with inhaled corticosteroids, correlated with more clinically aggressive RRP 29 . Similar to asthma, DM is a common comorbid condition in the United States that affects millions.…”
Section: Discussionmentioning
confidence: 99%
“…Given these results, it is important to understand intrinsic patient factors that affect patient susceptibility to RRP or severity of disease. Robb et al have reported evidence that the diagnosis of asthma, or its treatment with inhaled corticosteroids, correlated with more clinically aggressive RRP 29 . Similar to asthma, DM is a common comorbid condition in the United States that affects millions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to HPV type, age of onset has an important influence on the disease course of RRP . Finally, also comorbidity like asthma or gastroesophageal reflux disease (GERD) can worsen the clinical course of RRP …”
Section: Introductionmentioning
confidence: 99%
“…The final histo-pathology revealed a complicated squamous respiratory papilloma with superadded infection by aspirgellosis and actinomycosis. Few cases are reported like this case in the literature especially in immune-competent patients [39,40] . However, those patients reported in the literature had recurrent respiratory papillomas not like our patient who had it for the first time.…”
Section: Discussionmentioning
confidence: 87%